A study of the results of Using Board Games for teaching and learning an Introduction to Accounting-on-Accounting Equation: A Case Study of Accounting Students of Faculty of Business Administration and Liberal Arts, Rajamangala University of Technology Lanna Tak - Polpanumas, Anothai; tasao, Thunwarin (Journal of Industrial Business Administration, 2024)
The objectives of this research are (1) to compare academic achievement in accounting at the entry level; Using accounting games with a criterion of 80 percent (2) to study satisfaction by using soccer games to support the teaching of elementary accounting principles. Accounting The sample used in this study was undergraduate students in the field of accounting. Faculty of Business Administration and Liberal Arts Rajmangala Lanna Tak University of Technology, 203 people. Materials used include: Board games for teaching basic accounting techniques. Test of achievement of account balance and satisfaction survey scale used for descriptive analysis also used t-test. The research results found that Academic achievement using board games in the elementary accounting subject. Accounting equations After studying above the threshold of 80 percent at the statistical significance level of 0.010 and 0.050, the level of satisfaction with the use of board game media. For first-year accounting students, it was at a high level with a mean of 4.338 and a standard deviation of 0.795.